Homoparenting as a public health issue: a scoping review - Romeu Gomes; Tereza Setsuko Toma; Jessica De Lucca Da Silva; Fernando Meirinho Domene; Adriano da Silva (Universidade de São Paulo, 2023)
ABSTRACT OBJECTIVE To map global scientific production on homoparenting in the field of collective health or public health. METHODS In terms of methodological procedures, a scoping review was carried out, guided by the following question: What are the aspects addressed in global scientific production regarding homoparental families in the field of collective or public health? The searches were carried out in seven sources of scientific literature, including 58 studies, involving scientific articles and dissertations. The analytical treatment given to the studies, most of which were qualitative, followed the content analysis technique in the thematic modality. RESULTS The results indicate that the perceptions of homosexuals and professionals about the care provided and health services in general was the topic addressed by the largest number of studies (n = 31), followed by heteronormative context of health services (n = 26); disclosure of sexual orientation (n = 20); fertilization (n = 14); educational information and actions (n = 5). CONCLUSION Although the issue of same-sex parenthood has been discussed in some health sectors, there is awareness that it is necessary to rely on a consolidated basis through numerous studies when discussing this issue. It is concluded that, among other aspects, the scope of this review is not sufficiently problematized within the scope of health professionals' training and performance.